Increased range of motion but otherwise similar clinical outcome of arthroscopy over open osteoplasty for femoroacetabular impingement at midterm follow-up: A systematic review. Issue 3 (June 2022) - Migliorini, Filippo; Liu, Yu; Eschweiler, Jörg; Baroncini, Alice; Tingart, Markus; Maffulli, Nicola
Abstract: Background: A systematic review was conducted comparing patient reported outcomes measures (PROMs), functional scores, and the rate of complications between arthroscopic and open treatment for femoroacetabular impingement (FAI) at mid-term follow-up. Material and methods: This systematic review was performed according to the PRISMA guidelines. The literature search was performed in October 2020. All clinical trials treating FAI using open osteoplasty or arthroscopic surgery were considered for inclusion. Only articles reporting >12 months follow-up were included. Results: Data from 97 articles (9981 procedures) were collected. At a mean 19.2 months follow-up there was no difference between the two cohorts. At a mean follow-up of 38 months, the external rotation was increased in the arthroscopic group (P < 0.0001). The modified Harris Hip Score scored greater in favour of the open osteoplasty group (P = 0.04), as did the Hip Outcome Score - Activities of Daily Living subscale (P = 0.01). At a mean 45.1 months the arthroscopic group presented greater external rotation (P < 0.0001) and SF-12 Mental (P = 0.04). The modified Harris Hip Score was greater in favour of the open osteoplasty group (P = 0.03), as was the HOS-ADL (P = 0.01). Regarding complications, the arthroscopic group experienced lower rates of subsequent revisions (P < 0.0001). Conclusion: Based on the significant reduction of revisions-rate and significant increase in range of motion, arthroscopy treatment for the management of FAI may be recommended.